Fingertip and thumb tip wounds: changing algorithms for sensation, aesthetics, and function - Germann, Günter; Hrabowski, Manuel (The journal of hand surgery. European volume, 2017)
Management of fingertip and thumb tip injuries has recently undergone substantial changes. The time-proven traditional armamentarium of local flaps has been expanded and replaced by a wide variety of flaps. Simultaneous with the development of new flaps, the conservative treatment of fingertip and thumb tip injuries with semiocclusive dressings has also become a more acceptable treatment for these injuries. The excellent results with respect to restoring contour, sensibility of the pulp, and aesthetics of the finger justify this more tedious and time-consuming treatment of fingertip and thumb tip injuries. This article gives an update of the most commonly used flaps and the semiocclusive dressing treatments of fingertip and thumb tip injuries.